Training of Social Workers in the Countries of the European Union - Fesenko, N; Rubashka, V (Problems of Engineer-Pedagogical Education, 2019)
The article analyzes the mechanisms of realization of the state social policy. The historical conditions of formation of the common social policy of the European Union are determined. It was substantiated that the development of the economic sector of the member countries was the main direction of the foundation of a common Europe. The main objective of the countries which united and noted that in the 1957 Rome Treaty was the creation of a common market. It was believed that political and social integration would eventually follow. The article reveals an umber of issues of vocational training of highly skilled professionals for the sphere of social services. The main constituents and directions of realization of the European basis of social rights are generalized: equal opportunities and access to the labor market; fair working conditions; social protection and inclusion. The description of legislative initiatives concerning the mechanism of implementation of the component is given. The directions of implementation of the adopted European act are set out: the creation of a European Labor Organization, initiatives to ensure a balance between work and personal life of parents and guardians, a new Directive on transparent and predictable working conditions and reform of the rules for the coordination of social security. It is revealed that the main policy in the field of social protection of the EU is the Europe 2020 Strategy and an open method of coordination of social protection and social integration (OMC), which aims to promote social cohesion and equality through adequate, accessible and financially sustainable social protection, a system of social integration. Particular attention is paid to the analysis of the system of social protection of the European Union, the method of coordination of social protection and social integration. It is revealed that social policy at both national and supranational levels is an integral part of globalization processes. The concept of the social dimension of the European Union is defined; the peculiarities of membership in the EU and the possibilities of each member state regarding decision-making on matters which concern the budgets of social expenditures are described. The system of training of specialists for providing social services in the United Kingdom, France, Germany and the Netherlands is analyzed, the specific and common features of the process of training social workers in the specified countries are revealed.